Theories of Unemployment and its application in Ethiopia: A Review - Gebretsadik, Teklu (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
Unemployment is an integral part of a market economy, with socioeconomic consequences for the population of the countries in which these processes occur. For most of the able-bodied population growing unemployment normally means catastrophe. Unemployment often brings terrible consequences, such as declining incomes and purchasing power, which in turn leads to an inability to raise their living standards. For many emerging economies this phenomenon has the character of a disaster. The purpose of this article is to show the unemployment theories and applications of its significant, and which variables can define it. During the recent years, unemployment has risen high enough, and the opportunity to find a job for the working population is still quite an acute problem. The rise of prices is continuing rigorously, as it can see from increasing prices for goods and services. So, based on the study material, it‟s obvious that from the historical point of view the connection between job creation and unemployment does exist. Most of economists agree to the opinion that in the short-term, there is an inverse relationship between unemployment and inflation. As for the long-term, such a relationship is absent. Therefore, the government’s efforts to stimulate aggregate demand to increase the volume of GDP at full employment should lead to an increase in job creation.